Letter from World University Service on Opening of Hostels for Refugee Hungarian Students. 56/57 - General - 614 22.XI.56 - 170 - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): World University Service Letter from World University Service to UN reporting on opening of hostel for refugee Hungarian students in Vienna with support from International Rescue Committee and YW/YMCA. Efforts to resettle students have begun at hostel. Letter also discusses plans to open hostel in Switzerland, referred to as the Fribourg project, which will be able to accommodate at least 100 Hungarian students.